'Ici et par toute la terre': Paris, British universities and the French study abroad in the inter-war. (February 2023) - Michallat, Wendy
This article begins with the recommendations of the Leathes Report of 1916 in connection with the internationalisation of language study and the reasons why the ideal of transnational mobility was slow to take root in language departments in the UK. It examines how the provision of safe, secure and affordable accommodation for women students was an effective counter to alarmist stay-at-home tales. And it looks at how feminist educators campaigned to promote international learning and teaching opportunities for women scholars. It argues that the Leathes concept of an 'immersion' experience conflicted with the University of Paris's interpretation of the 'internationalisation' of study. The Cité universitaire (CU) project, launched in the 1920s, offered the possibility for the easy placement of a growing number of students from the British red-brick universities in particular. But the conviction of British academics that the proposed Collège Franco-Britannique should house both French and British students was at odds with the University of Paris's concept of a campus of representative national houses in which only students of that country were permitted to live. It concludes that the mobilisation of the profession into subject bodies was a key factor in the evolution of study abroad programs and more broadly in the consolidation of 'modern studies' in the new civic and red-brick universities across Britain.